Reproductive physiology, and physical and sexual development of female offspring born to diabetic dams - Spadotto, Raquel [UNESP]; Damasceno, Débora Cristina [UNESP]; Godinho, Antônio F. [UNESP]; Amorim, Elaine Manoela Porto; Perobelli, Juliana Elaine; Kempinas, Wilma De Grava [UNESP] (My University, 2012)
Objectives: The objective of this study was to evaluate physical and sexual development and reproductive physiology in female rat offspring that developed in hyperglycemia conditions in utero and during lactation. Materials and methods: Maternal diabetes was induced in female rats by a single IV injection of streptozotocin before mating. Female offspring development was evaluated by means of the following parameters: physical development; age of vaginal opening and first estrus; weight and histological evaluation of uterus and ovaries; duration of the estrous cycle, sexual behavior, and fertility after natural mating. Results: In the female offspring, maternal diabetes caused delays in initial physical development; diminution in ovary weight and number of follicles; and inferior reproductive performance compared with the control group. Conclusions: The exposure to hyperglycemia in uterus and during lactation caused delays in physical and sexual development, and affected the reproductive physiology of female rats negatively.

Objetivos: O objetivo deste estudo foi avaliar o desenvolvimento físico e sexual e a fisiologia reprodutiva de ratas que se desenvolveram em condições hiperglicêmicas in utero e lactação. Materiais e métodos: Para induzir o diabetes nas ratas, foi utilizada estreptozotocina em dose única via intravenosa antes do acasalamento. A prole feminina foi avaliada por meio dos seguintes parâmetros: o desenvolvimento físico; a idade de abertura vaginal e do primeiro estro, peso e avaliação histológica do útero e ovários; a duração do ciclo estral, o comportamento sexual e a fertilidade após acasalamentos naturais. Resultados: O diabetes materno provocou, na prole feminina, retardo no desenvolvimento físico; diminuição do peso dos ovários e do número de folículos; a performance reprodutiva foi inferior à do grupo controle. Conclusões: Concluiu-se que a exposição aos meios intrauterino e lactacional hiperglicêmicos provocou retardo no desenvolvimento físico e sexual e prejudicou a fisiologia reprodutiva de ratas.
Desenvolvimento físico, sexual e fisiologia reprodutiva da prole feminina de ratas diabéticas
Keywords: Sexual behavior; Physical development; Diabetes; Female reproductive physiology; Female rat; Streptozotocin; Comportamento sexual; Desenvolvimento físico; Diabetes; Fisiologia reprodutiva feminina; Rata; Estreptozotocina